Dead time duration and active reset influence on the afterpulse probability of InGaAs/InP single-photon avalanche diodes - Losev, Anton V.; Zavodilenko, Vladimir V.; Koziy, Andrey A.; Filyaev, Alexandr A.; Khomyakova, Kristina I.; Kurochkin, Yury V.; Gorbatsevich, Alexander A. (IEEE journal of quantum electronics)
We have performed a detailed study of the dependence of afterpulse probability in InGaAs/InP sine-gated SPAD on the dead time and the existing approach for its implementation. We demonstrated an electrical scheme combining sinusoidal gating and active reset. We have shown when such solutions are beneficial from the key distribution point of view, and enough to use a simple scheme with a snatching comparator. We have also proposed a precise method for measuring the afterpulse and presented a model describing the non-markovian dynamic of this effect. We have demonstrated that our afterpulsing measurement approach makes these measurements less dependent on the parameters of the flow of the diode and the laser pulses' power changes, in contrast to the other methods considered in this paper.